Waugh’s syndrome in an adult: report of a very rare disease - Poras Chaudhary; Meenakshi Rao; Moninder P. Arora (Clinics and Practice, 2012)
The authors report a case of Waugh’s syndrome in an adult. Waugh’s syndrome is rare in adults as most of the cases present in paediatric age group. We have discussed treatment options and it is suggested that the possibility of Waugh’s syndrome should always be kept in mind when a case of intussusception is being treated by either operative or non-operative method.